2004
DOI: 10.2337/diacare.27.1.277
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Prognostic Value for Coronary Disease Risk Between the U.K. Prospective Diabetes Study and Framingham Models

Abstract: References 1. Aso Y, Okumura K-I, Takebayashi K, Wakabayashi S, Inukai T: Relationships of plasma interleukin-18 concentrations to hyperhomocysteinemia and carotid intima-media wall thickness in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…For 14 comparisons, the authors either claimed that both models had poor or equal discriminatory ability or did not comment on their relative performance [16,19,29,[31][32][33][34]36]. In one pair wise comparison, the authors favored the general population model (Framingham equation [37]) over a diabetes-specific risk model. In two articles including six pair wise comparisons, the authors favored the models they had themselves developed [19,24].…”
Section: Discussionmentioning
confidence: 99%
“…For 14 comparisons, the authors either claimed that both models had poor or equal discriminatory ability or did not comment on their relative performance [16,19,29,[31][32][33][34]36]. In one pair wise comparison, the authors favored the general population model (Framingham equation [37]) over a diabetes-specific risk model. In two articles including six pair wise comparisons, the authors favored the models they had themselves developed [19,24].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that Framingham coronary heart disease (CHD) risk prediction equation underestimates risk among people with Type 2 diabetes [1][2][3][4][5][6]. Proposals to address this issue have included: adding a weighting or calibration factor to the predicted Framingham risk [7,8]; using a lower CHD risk threshold [9,10] or using the United Kingdom Prospective Diabetes Study (UKPDS) CHD risk prediction equation which was derived from a large cohort of people with newly diagnosed diabetes [1].…”
Section: Introductionmentioning
confidence: 99%
“…1). Protopsaltis et al [98] and McEwan et al [45] also found poor prediction with the UKPDS risk engine. Guzder et al [87] observed better estimation of CHD risk using the UKPDS method compared with the Framingham-Anderson method.…”
Section: Risk Scoring In Diabetesmentioning
confidence: 99%
“…Framingham risk scoring methods tend to underestimate risk in diabetic populations [45,87,98] (Fig. 1).…”
Section: Risk Scoring In Diabetesmentioning
confidence: 99%